Electroplating of Nanostructures 2015
DOI: 10.5772/61456
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Thin Films for Low-cost Solar Cells

Abstract: This chapter endeavors to bring to the reader the potential of electrochemical deposition processes to develop low cost solar cells. The targeted photovoltaic absorbers are largely inorganic compound semiconductors containing earth abundant elements and satisfying the physical criteria of band gap and dopability. Electrodeposition, being an well established chemical process having its inherent capability for a large productions, should also be applied to develop various low cost solar cells, such as Cu ZnSnS ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…At last, a gold film was deposited on the CdTe as the back contact. The solar cell achieved a solar-to-power conversion efficiency as high as 9.35% [76]. Such an efficiency is very impressive.…”
Section: Cdtementioning
confidence: 93%
“…At last, a gold film was deposited on the CdTe as the back contact. The solar cell achieved a solar-to-power conversion efficiency as high as 9.35% [76]. Such an efficiency is very impressive.…”
Section: Cdtementioning
confidence: 93%
“…The reduction of Pb ions generally leads to a positive charge in the solution, resulting in a neutral lead atom on the cathode. As will be shown later, the higher the concentration of Pb ions, the greater the number of adatoms removed and the more they eventually form a lattice [13].…”
Section: Cyclic Voltammetry Studymentioning
confidence: 82%
“…Maintaining a constant temperature will ensure homogeneous dissolution across the total anode area during the anodization process. Abhijit Ray [13], however, reported that high temperatures speed up the chemical dissolution process. Consequently, working temperatures should usually be kept fairly low(~ambiant) so that the oxide does not dissolve completely.…”
Section: Cyclic Voltammetry Studymentioning
confidence: 99%
“…The weak adhesion and thin coatings lead to a setback with industrial applications. 41 Hence, other syntheses may prove useful.…”
Section: Electrodeposition Techniquementioning
confidence: 99%